Robust Medical Monitor Design - Weimer, James; Sokolsky, Oleg; Insup Lee (2015 International Conference on Healthcare Informatics, 2015)
Summary form only given. With recent advances in low-power low-cost communication, sensing, and actuation technologies, Medical Cyber Physical Systems (MCPS) have revolutionized automated medical diagnostics and care. With this revolution, dawns a new era of medical monitoring where fusing measurements from multiple devices provides unprecedented early detection of critical conditions. However, often explicit models and/or rich training data relating available measurements to the critical conditions are unavailable or impractical. Under these troublesome scenarios, this tutorial presents a parameter invariant approach to medical monitor design which has been successful in developing monitors for conditions related to hypoxia, diabetes, and hypovolemia. Owing its mathematical origin to the robust radar signal processing literature, the parameter-invariant approach to medical monitor design is presented as consisting of three parts: (1) foundations of parameter-invariant design, (2) modeling physiological processes for monitoring, and (3) constant false alarm rate (CFAR) testing. To illustrate each component, the tutorial makes extensive use of case study monitors related to medical alarms for hypoxia, hypovolemia, and hypoglycemia.